Prevalence of aflatoxigenic fungi and aflatoxins on commercial and formulated goat's feed, and aflatoxin M1 carryover in goat's milk - Azman, Nur Izzati (2020)
At present, the consumers’ preference over cow’s milk has steadily shifted towards goat’s milk due to its many newly-found benefits. In Malaysia, largescale commercial goat’s milk production is still relatively new and mainly managed by the small and medium enterprises (SMEs). Among the major problems faced by Malaysian goat farmers is feed contamination by the aflatoxigenic Aspergillus flavus and A. parasiticus. The hot and humid climate of Malaysia further exacerbates the fungal proliferation which leads to the production of aflatoxins, especially aflatoxin B1 (AFB1). Upon ingestion, AFB1 is bio-transformed into AFM1 which is transferrable to infants during breastfeeding. AFM1 causes stunted growth and delayed development in infants and children. Although worldwide surveillance studies have been done on AFM1 contamination in milk and milk products, Malaysian-based data are scarce. Furthermore, with the booming of goat’s milk industry in Malaysia, numerous researches are being conducted, including feed formulation, for the goats’ health improvement and maintenance. Nevertheless, the safety and quality of the formulated feed must still be ensured. Therefore, the objectives of the present work were (i) to determine the prevalence of aflatoxigenic Aspergillus spp. on commercial and formulated goat’s feed samples; (ii) to determine the occurrence of aflatoxins present in commercial and formulated goat’s feeds; and (iii) to determine the occurrence of aflatoxin M1 present in goat’s milk samples and to establish the relationship between AFB1 present in commercial and formulated goat’s feeds and their carryover rate in goat’s milk as AFM1. Three commercial goat farms (Farms A, B, C) were selected to supply the commercial goat’s feed and goat’s milk over a period of three months (i.e., does’ common lactation period), while one farm involved in novel feed formulation was selected to supply the formulated goat’s feed and goat’s milk. The total number of goat’s feed samples was 60, and goat’s milk 120. Enumeration of fungal loads using Dichloran Rose Bengal Chloramphenicol agar showed that Farm C goat’s concentrate sample yielded the highest total fungal load at log 7.071 ± 0.03 CFU/g. Fungal identification on Aspergillus flavus and A. parasiticus agar revealed that 48.33% (n = 29 of 60) feed samples were positive for A. flavus and A. parasiticus with goat’s concentrate from Farm B yielded the highest load of A. flavus and A. parasiticus at log 3.206 ± 0.05 CFU/g. Enzyme-linked immuneassay (ELISA) was performed to quantify total aflatoxins in goat’s feed, and AFM1 in goat’s milk, while high performance liquid chromatography (HPLC) was used to quantify AFB1, AFB2, AFG1, and AFG2 in goat’s feed, and AFM1 in goat’s milk. ELISA results revealed that 76.67% (n = 46 of 60) goat’s feed samples were contaminated with total aflatoxins (0.050 to 4.658 ng/g), while HPLC results revealed that 11.67% (n = 7 of 60) goat’s feed samples were contaminated with AFB1 (0.139 to 28.18 ng/g), AFB2 (6.78 ng/g), and AFG1 (1.71 to 54.99 ng/g). AFG2 was not detected. One feed sample from Farm A was found with AFB1 higher than the maximum European Union (EU) regulatory limit. Comparing to the other farms, Farm A generally had higher aflatoxin contamination. High relative humidity and temperature during sampling at Farm A could have led to this contamination as these ecophysiological factors are conducive for aflatoxin production by Aspergillus spp. ELISA results further revealed that 46.67% (n = 56 of 120) goat’s milk samples were positive for AFM1 (0.052 to 0.177 ng/mL), while HPLC revealed that no goat’s milk sample was contaminated with AFM1. Following the positive results of AFM1 in goat’s milk samples, the AFB1 in goat’s feed from the same week when the milk was sampled was obtained, and the carryover rate of AFM1 was estimated. The carryover efficiency from AFB1 in feed into AFM1 in milk was found within the range of 0.12 to 11.54%. The amount of AFM1 detected in goat’s milk samples did not exceed the Malaysian regulatory limit of 0.5 ng/mL, but exceeded the EU regulatory limit of 0.5 ng/mL.